2021
DOI: 10.3390/rs13245166
|View full text |Cite
|
Sign up to set email alerts
|

UAV- and Machine Learning-Based Retrieval of Wheat SPAD Values at the Overwintering Stage for Variety Screening

Abstract: In recent years, the delay in sowing has become a major obstacle to high wheat yield in Jiangsu Province, one of the major wheat producing areas in China; hence, it is necessary to screen wheat varieties are resilient for late sowing. This study aimed to provide an effective, fast, and non-destructive monitoring method of soil plant analysis development (SPAD) values, which can represent leaf chlorophyll contents, for late-sown winter wheat variety screening. This study acquired multispectral images using an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…Furthermore, a comparison in terms of the optimal number of variables selected revealed that PCA selected 35 variables, LASSO selected 35 variables, and RFE selected 31 variables (Table 6). The number of optimal variables selected using RFE is relatively small, which is consistent with the research of (Wang et al, 2021), but the smallest number of variables selected does not represent the best performance of model estimation. Additional studies should be conducted to assess the association between the number of variable choices and model estimation performance.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, a comparison in terms of the optimal number of variables selected revealed that PCA selected 35 variables, LASSO selected 35 variables, and RFE selected 31 variables (Table 6). The number of optimal variables selected using RFE is relatively small, which is consistent with the research of (Wang et al, 2021), but the smallest number of variables selected does not represent the best performance of model estimation. Additional studies should be conducted to assess the association between the number of variable choices and model estimation performance.…”
Section: Discussionsupporting
confidence: 82%
“…Specifically, to further evaluate the effects of source and bank organs on the AGB estimation model and the GY estimation model, experiments with multiple wheat genotypes as well as other crop types under different environmental conditions are also needed (Geipel et al, 2014; Gong et al, 2018; Peng et al, 2019; Wan et al, 2020). On the contrary, due to the limitations of proximity sensors, UAV technology is becoming more and more commonly used for crop phenotype monitoring (Wan et al, 2020; Wang et al, 2021; Xu et al, 2021; Yu et al, 2022; Zhu et al, 2019), so in the next research, UAV technology and proximity sensors can be combined to obtain ultra‐high‐resolution images in multiple directions for more accurate crop yield estimation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflectance at a green wavelength (used in GCVI and GNDVI) was more sensitive to fluctuation in leaf chlorophyll, which was closely correlated with canopy nitrogen concentration when compared to reflectance at a red wavelength (Zhao et al 2018;Lobell et al 2020;Wang et al 2021). In comparison to standard EVI and NDVI, GCVI and GNDVI are better at capturing nutritional status which accounts for final yield (Burke and Lobell 2017).…”
Section: Comparing the Correlation Of Vis In Oil Palm Yield Predictionmentioning
confidence: 99%
“…With the ongoing development of sensor and image processing technologies, machine learning-an essential area of computer science-is now extensively applied in all facets of precision agriculture research, including leaf dynamic monitoring [24]. Moreover, machine learning methods are more precise and effective than conventional linear regression models and have been frequently utilized to create prediction models to link image data and biological parameters [25]. There have been few soybean studies to explore the prediction effect of various machine learning models on the leaf parameters of a single plant throughout its entire growth period.…”
Section: Introductionmentioning
confidence: 99%